1967
DOI: 10.1210/jcem-27-4-473
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Adrenal Corticosteroid Synthesis by Aminoglutethimide: Studies of the Mechanism of Action1

Abstract: The first of the three volumes of this encyclopaedic dictionary of dermatology was reviewed in this Journal in April 1971. The second volume covers eczema, including occupational dermatoses, seborrhoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
69
0
2

Year Published

1972
1972
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(74 citation statements)
references
References 0 publications
3
69
0
2
Order By: Relevance
“…Treatment of cultures with aminoglutethimide, an inhibitor of the conversion of cholesterol to pregnenolone (24), reduced the ACTH and monobutyryl cyclic AMP (cAMP)-stimulated level of steroid production to the nonstimulated level seen in the absence of aminoglutethimide (Table I). Under these conditions, ACTH and monobutyryl cAMP continued to reduce [3H]thymidine incorporation into DNA to the same extent as in the non-aminoglutethimide-treated cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of cultures with aminoglutethimide, an inhibitor of the conversion of cholesterol to pregnenolone (24), reduced the ACTH and monobutyryl cyclic AMP (cAMP)-stimulated level of steroid production to the nonstimulated level seen in the absence of aminoglutethimide (Table I). Under these conditions, ACTH and monobutyryl cAMP continued to reduce [3H]thymidine incorporation into DNA to the same extent as in the non-aminoglutethimide-treated cultures.…”
Section: Resultsmentioning
confidence: 99%
“…This therapeutic regime was derived with the aim of suppressing adrenal androgen synthesis (Lipton et al, 1974;Wells et al, 1978) which was expected to result from previously reported inhibition by AG of the conversion of cholesterol to pregnenolone by 20,22-desmolase (Cohen, 1967;Dexter et al, 1967). HC was added to the regime to prevent a rise in adrenocorticotrophic hormone, which would result from suppression of cortisol synthesis, and which might overcome the enzyme block (Wells et al, 1978).…”
mentioning
confidence: 99%
“…The response of some patients to cortisone alone (Miller & Hinman, 1954) or to bilateral adrenalectomy (Mahoney & Harrison, 1972;Hendry, 1974) suggests that in some cases the tumour may retain sensitivity to residual adrenal androgens. Aminoglutethimide is an inhibitor of several enzymes involved in adrenal steroid synthesis (Dexter et al, 1967) and in prostaglandin metabolism (Harris et al, 1983c). The combination of aminoglutethimide and hydrocortisone had previously been reported both to reduce circulating levels of adrenal androgen and, in small numbers of patients, to induce responses in hormone-relapsed advanced prostatic cancer (Robinson et al, 1974;Sanford et al, 1976).…”
mentioning
confidence: 99%